Diverse linkages between green bonds and equity indices of developed and developing economies - Pillai, Deepa; Doifode, Adesh; Parashar, Neha; Bhosale, Trupti; Ghosh, Aniruddha; Surapalli, Sandhya; Sharma, Rahul (International Journal of Management and Sustainability, 2024)
This paper investigates the dynamic conditional correlations and volatility spillovers between global stock markets and international green bonds. Envisaging the linkages between the emerging green bond markets and global equities given the unforeseen global pandemic. We use R software to run bivariate VAR-BEKK GARCH and BEKK GARCH models to investigate the time-varying conditional volatility between global stock indices and green bond indices. Daily prices of all variables from October 2014 to April 2023 are sourced from the Bloomberg database. The short-term influence of past events, as well as the long-term persistence of green bonds, on the current conditional volatility of global equity indices of developed and emerging economies is observed. Whereas from equity markets to green bond indices, the short-term as well as long-term impact is confined to only 2-3 indices. The results provide future direction for policymakers, researchers, and global investors in hedging and creating an optimal portfolio.